2011
DOI: 10.1016/s1734-1140(11)70582-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic effect of phloretin on cisplatin-induced apoptosis in HEI-OC1 auditory cells

Abstract: Cisplatin is a highly effective chemotherapeutic agent, but it has significant ototoxic side effects. Apoptosis is an important mechanism of cochlear hair cell loss following exposure to cisplatin. The present study examined the effects of phloretin, a natural polyphenolic compound found in apples and pears, on cisplatin-induced apoptosis. We found that phloretin induced the expression of heme oxygenase-1 (HO-1) protein in a concentration- and time-dependent manner. Phloretin induced nuclear factor-E2-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…By contrast, Bcl-2 protein disrupts this process and decreases apoptosis (40). It has also been demonstrated that Bcl-2 expression is reduced while that of Bax is increased in HECI-OC1 cells pre-treated with ZnPP (36). Thus, we hypothesized that pre-treatment with ZnPP would promote the release of cytochrome c and the activation of the mitochondrial death cascade.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…By contrast, Bcl-2 protein disrupts this process and decreases apoptosis (40). It has also been demonstrated that Bcl-2 expression is reduced while that of Bax is increased in HECI-OC1 cells pre-treated with ZnPP (36). Thus, we hypothesized that pre-treatment with ZnPP would promote the release of cytochrome c and the activation of the mitochondrial death cascade.…”
Section: Discussionmentioning
confidence: 94%
“…However, this was not observed in the control and HIR groups. mechanisms against cisplatin-induced apoptosis (36). Another study found that the induction of HO-1 ameliorated hepatocyte apoptotic activity and oxidative damage in rats with hyperthyroidism, and decreased the expression of cytochrome c, caspase-3, caspase-8 and Bax.…”
Section: Discussionmentioning
confidence: 97%
“…CoPPIX inhibits cisplatin-induced death in the HEI-OC1 auditory-derived cell line (Kim et al 2006a(Kim et al , 2009So et al 2006So et al , 2008Choi et al 2007Choi et al , 2008Choi et al , 2011Gao et al 2010). HO-1 expression has been reported in cochlear hair cells and stria vascularis following a variety of stressors, including noise stress, heat stress, and pharmacological induction (Fairfield et al 2004;Lopez et al 2008;Kim et al 2009;Matsunobu et al 2009;Fetoni et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological induction of HO-1 is protective against multiple stresses in many tissue types, including ischemia-reperfusion injury in liver and retina (Tsuchihashi et al 2007;Sun et al 2010). Several studies have demonstrated that inducers of HO-1 protect against cisplatin-induced death in the HEI-OC1 auditory cell line (Kim et al 2006a(Kim et al , 2009So et al 2006So et al , 2008Choi et al 2007Choi et al , 2008Choi et al , 2011Gao et al 2010). We have shown that HO-1 induction inhibits hearing loss and hair cell death caused by aminoglycoside antibiotics (Francis et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the effects are due to estrogenic activity of the substance [13,14,16]. At low concentrations, phloretin has been shown to protect against apoptosis [17]. At high concentrations, phloretin may trigger apoptosis and thus counteract malignancy [1,2,18,19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%